Association between the candidate susceptibility gene ACVR2A on chromosome 2q22 and pre-eclampsia in a large Norwegian population-based study (the HUNT study) - Roten, L.; Johnson, M.; Forsmo, S.; Fitzpatrick, E.; Dyer, T.; Brennecke, S.; Blangero, J.; Moses, Eric; Austgulen, R. (Nature Publishing Group, 2009)
Genome-wide scans in Icelandic, Australian/New Zealand and Finnish pedigrees have provided evidence for maternal susceptibility loci for pre-eclampsia on chromosome 2, although at different positions (Iceland: 2p13 and 2q23, Australia/New Zealand: 2p11-12 and 2q22, Finland: 2p25). In this project, a large population-based (n = 65000) nested case-control study was performed in Norway to further explore the association between positional candidate genes on chromosome 2q and pre-eclampsia, using single-nucleotide polymorphisms (SNPs). DNA samples from 1139 cases (women with one or more pre-eclamptic pregnancies) and 2269 controls (women with normal pregnancies) were genotyped using the Applied Biosystems SNPlex high-throughput genotyping assay. In total, 71 SNPs within positional candidate genes at 2q22-23 locus on chromosome 2 were genotyped in each individual. Genotype data were statistically analysed with the sequential oligogenic linkage analysis routines (SOLAR) computer package. Nominal evidence of association was found for six SNPs (rs1014064, rs17742134, rs1424941, rs2161983, rs3768687 and rs3764955) within the activin receptor type 2 gene (ACVR2A) (all P-values <0.05). The non-independence of statistical tests due to linkage disequilibrium between SNPs at a false discovery rate of 5% identifies our four best SNPs (rs1424941, rs1014064, rs2161983 and rs3768687) to remain statistically significant. The fact that populations with different ancestors (Iceland/Norway-Australia/New Zealand) demonstrate a common maternal pre-eclampsia susceptibility locus on chromosome 2q22-23, may suggest a general role of this locus, and possibly the ACVR2A gene, in pre-eclampsia pathogenesis.